THE URGENCY OF DIGITAL BROADCASTING FOR PUBLIC INTEREST TO GET QUALITY BROADCASTING SERVICES: (STUDY ON TVRI NTB LOVERS GROUP) - Saudi, Yusron; Rahmawati, Endang (Universitas Islam Negeri Mataram, 2023)
The transition from analog to digital broadcasting has been mandated for West Nusa Tenggara (NTB) Province. Numerous stakeholders are involved in the dissemination of information about the relocation of broadcasting in NTB. The spread of information about broadcasting migration and the pressing need for digital broadcasting are investigated in this study using the qualitative technique. The study's findings show that the government used a number of broadcasting organizations (TV and radio) to disseminate information about the migration to digital television in NTB. The public has endorsed this in order to acquire broadcasting services of a higher caliber. This switch to broadcasting is the best move for making optimum use of frequency and fostering the development of the digital economy and industry.